"Clay" or a model of repetition - Heleno Godoy (Ilha do Desterro)
Two things have called the critics' attention ) in James Joyce's "Clay," the tenth story in Dubliners: the symbolic duplicity of Maria, at the same time the witch and the Virgin, and the omission, when Maria sings "I Dreamt that I Dwelt," of the second stanza of the song, the hit tune from the opera The Bohemian Girl, libretto by Alfred Bunn and music by Michael William Balfe. 2 Although Joyce presents this omission in an ambiguous way ("she sang again," "no one tried to show her her mistake"3), much attention has been given, in critical analyses of the story, to the stanza which is not sung, where there are references to marriage, something Maria, old and ugly, could not aspire to.